Corruption in Mexico: A Historical Legacy - Nieto, Nubia (Social Science Diliman: A Philippine Journal of Society and Change; Vol 10 No 1 (2014))
Among the many consequences of colonialism that are still present in postcolonial societies are corruption and the lack of strong institutions to fight against this phenomenon. What used to be unequal power relations between the colonizers and the colonies have been replaced by the dominance of the local elites over ordinary citizens, who have practically given the former a lot of leeway to commit acts of corruption with a sense of impunity and without regard for accountability. One case in point is Mexico which, in recent times, has made international news headlines because of incidences of drug trafficking, violence, and corruption in the country. This article delineates the historical relationship between corruption and colonialism, and how these forces have shaped Mexican culture. The discussion tackles the presence of corruption since the colonial times to the present. Specif ically, it starts with an analysis of the role of colonialism in the incidence of corruption. Secondly, it describes the discrepancy between the law and its application, from the arrival of the Spanish colonizers to the present. Finally, it examines the cultural, educational, and social challenges that should be addressed in order to surmount the colonial legacies that breed corruption. Keywords: Corruption, colonialism, Mexico, elites, culture